Is Dance a Language? Movement, Meaning and Communication - Bannerman, Henrietta (Edinburgh: Edinburgh University Press, 2014)
RESUMEN: This essay explores western theatre dance as meaningful, despite its difference from language or discourse. I contend that although like language dance communicates through cultural codes, it does not convey literal messages but then neither is dance dominated by a requirement for factual specificity. I argue, however, that dance is structured like a language and I provide an analysis of the methods according to which language functions on an everyday basis. I review linguistic categories and argue for their counterparts in dance including vocabulary and syntax, the utterance and the speech act. The speech act is an important instance of language use which I hold is represented in dance; and in addressing this topic I shed new light on the performative quality of dance. The various theoretical issues discussed in the essay are illustrated by examples taken from modern and postmodern dance as well as from classical ballet.